(untitled) (International journal of artificial intelligence, 2025)
There is a speech about some aspects of teaching students for making up a composition at the lessons of applied art. It is stated, the main aim of given work is a bringing up (nurture) of sense world’s beauty, love for the finest, stretching to the beauty of man soul.